The Leader Effective Communication in Solving Employee Conflict; REACH Analysis - Citagita Ramadhini; Leonard Adrie Manafe (International Journal of Economics Development Research (IJEDR), 2022)
Communication is the main key in building good relationships between people. Effective communication aims to make it easier for others to convey messages that are notified by the messenger. Effective communication is very important in resolving conflicts in employees. The study purpose is to describe the leadership effective communication in solving conflicts among employees at the printing company namely CV. Primasakti Copy Center (PCC) using REACH analysis (Respect, Empathy, Audible, Clarity, Humble). The research uses qualitative methods. Data collection techniques were carried out through interviews, direct observation, and documentation. This study involved eight informants consisting of company leaders and employees. The results showed that the company's leadership had implemented effective communication using REACH analysis in solving employee conflicts. The most dominant effective communication indicator applied by company leaders is the respect indicator, due to basically humans want to be appreciated and considered important. Keywords: Effective Communication, Employee Conflict, REACH Analysis